STRATEGI PENGEMBANGAN BISNIS DALAM MENGHADAPI PERSAINGAN BISNIS INSURANCE TECHNOLOGY (INSURTECH) DI INDONESIA - Reimond Hasangapan Mikkael Napitupulu; Hendrik S Nadapdap; Wahyu Maulana; Septiawan Pratama (JURNAL LENTERA BISNIS, 2025)
This research aims to analyze PT Asuransi Jiwa Nasional's business development strategy in responding to the challenges posed by the emergence of insurance technology startup companies (InsurTech) in Indonesia. Through a qualitative approach, this research reveals that PT Asuransi Jiwa Nasional has made a number of efforts to adapt, such as developing digital products, improving technology-based customer service, and establishing strategic partnerships with technology companies. However, this research also identified several challenges that companies face, such as internal resistance to change and limited technological infrastructure. It is hoped that the results of this research can contribute to insurance companies in formulating more effective strategies to compete in the digital era.